Transition-Metal-Free, Intermolecular Azidoheteroarylation of Alkenes: Efficient Access to β-Azidoalkylated Quinoxalinones and Preliminary Antifungal Evaluation Against Magnaporthe grisea - Du, Yiming; Chen, Yue; Liu, Yun-Lin; Qin, Weiwei; Li, Zhaodong (Synthesis, 2020)
An efficient, PhI(OAc)2-mediated, radical azidoheteroarylation of alkenes under transition-metal-free conditions is reported by employing TMSN3 and quinoxalin-2(1H)-ones as coupling partners. This domino reaction allows an eﬃcient synthesis of valuable orangoazides containing quinoxalin-2(1H)-one derivatives and could be extended to phosphinyl-alkylated quinoxalin-2(1H)-one in a single step in moderate to excellent yields under mild conditions, as demonstrated by the preliminary antibacterial evaluation against Magnaporthe grisea for the first time. Mechanistic studies revealed that this transformation undergoes a cascade addition pathway controlled by a polar radical.
Keywords: radical; domino; difunctionalization; azide; transition-metal-free